2020
DOI: 10.3390/cancers12061492
|View full text |Cite
|
Sign up to set email alerts
|

Development of a VLP-Based Vaccine Displaying an xCT Extracellular Domain for the Treatment of Metastatic Breast Cancer

Abstract: Metastatic breast cancer (MBC) is the leading cause of cancer death in women due to recurrence and resistance to conventional therapies. Thus, MBC represents an important unmet clinical need for new treatments. In this paper we generated a virus-like particle (VLP)-based vaccine (AX09) to inhibit de novo metastasis formation and ultimately prolong the survival of patients with MBC. To this aim, we engineered the bacteriophage MS2 VLP to display an extracellular loop of xCT, a promising therapeutic target invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…A bacteriophage MS2 VLP-based vaccine that displayed the extracellular loop of xCT transporter on its surface was used to treat mice carrying metastatic breast cancer cells. The treated animals produced high levels of specific antibodies and reduced metastasis [200]. Bolli et al developed the AX09-0M6 as a VLP-based vaccine platform by displaying of the human xCT extracellular domain (ECD6) on its surface.…”
Section: Vlp-based Vaccines Developed Against Breast Cancermentioning
confidence: 99%
“…A bacteriophage MS2 VLP-based vaccine that displayed the extracellular loop of xCT transporter on its surface was used to treat mice carrying metastatic breast cancer cells. The treated animals produced high levels of specific antibodies and reduced metastasis [200]. Bolli et al developed the AX09-0M6 as a VLP-based vaccine platform by displaying of the human xCT extracellular domain (ECD6) on its surface.…”
Section: Vlp-based Vaccines Developed Against Breast Cancermentioning
confidence: 99%
“…These NK cells in the immune infiltrate can mediate an antibody-dependent cellular cytotoxicity (ADCC) via the recognition of anti-xCT IgG2a antibodies induced by vaccination [ 55 ]. In a similar way, a newer VLP vaccine that displays the third extracellular domain of xCT (ECD3), whose sequence is longer than that of ECD6, resulting in a major oligoclonal antibody response, can neutralize xCT function and impair breast cancer cell proliferation and metastasization [ 61 ]. Finally, the bovine herpesvirus 4 (BoHV-4)-based anti-xCT vaccine, which exploits a safe viral vector that confers immunogenicity to tumor antigens, has proven to be effective in impairing lung metastasis and inducing T lymphocyte activation, anti-xCT antibody production and ADCC in mouse mammary cancer models [ 53 ].…”
Section: The Cystine/glutamate Antiporter Xctmentioning
confidence: 99%
“…Therefore, xCT contributes to the maintenance of a reducing TME that may preserve HMGB1 ability to activate TLR2 [ 103 ]. We have previously demonstrated that xCT protects breast CSCs from oxidative stress and chemotherapy, and we have developed different anti-xCT vaccines that decrease tumor growth and metastasis in breast cancer mouse models [ 76 , 101 , 102 , 104 , 105 ]. We hypothesize that the ability of xCT immunotargeting to inhibit the HMGB1/TLR2 axis may contribute to its therapeutic activity and suggest that it would be worth developing combined therapies targeting these two mechanisms responsible for tumor survival and progression.…”
Section: Effect Of Chemo and Radiotherapy On Tlr2 Activationmentioning
confidence: 99%